The Effect of Primary Family Caregiver Empowerment Program on the Activity of Daily Living Caring Behaviors of Cerebrovascular Disease Homebound Patients in Community, Bangkok - Pansanae, Nipa; Jewpattanakul, Yupa; Rerkluenrit, Juntima (Journal of The Royal Thai Army Nurses, 2023)
The pre-post two groups quasi-experimental research aimed to determine the effect of empowerment program on the activity of daily living care behaviors among primary family caregivers of homebound cerebrovascular disease patients. Gibson’s empowerment concept was used as the conceptual framework. The participants were 76 primary family caregivers of homebound cerebrovascular disease patients aged 18-60 years and living in community of Bangkok. Thirty-eight caregivers were randomly assigned sampling without replacement. For each group, the data was collected via the demographic data questionnaire, the perceived empowerment of primary caregiver questionnaire, the activity of daily living behavior questionnaire, and the empowerment program. The six weeks program was designed to empower the experimental group for caring patients in activity of daily living. Experimental caregiver group activities were organized for exchange caregiving experience, providing stroke instructions, demonstration care practices, reflect care activities, giving handbook, providing patient caring, and home visit. In addition, calling and sending short messages. The data was analyzed using independent t-test, Paired t-test, and analysis of covariance statistics. The findings revealed that the experimental group had higher mean scores of activities of daily living care behaviors than the control group with statistical significance (p < .01). In addition, the mean post-test score for the activity of daily living performance among primary caregivers in the experimental group was higher than before attending the program with statistical significance (p < .01).